A smartphone based attentive eating intervention for energy intake and weight loss: results from a randomised controlled trial - Victoria Whitelock; Inge Kersbergen; Suzanne Higgs; Paul Aveyard; Jason C. G. Halford; Eric Robinson (BMC, 2019)
Abstract Background Laboratory studies suggest that eating more 'attentively' (e.g. attending to food being eaten and recalling eating episodes) can reduce food intake among participants with both healthy weight and overweight. The aim of this trial was to assess whether a smartphone application that encourages a more attentive eating style reduces energy intake and promotes weight loss. Methods In an open-label, single centre, parallel groups, individually randomised controlled trial, 107 adults with overweight/obesity in Merseyside, UK used an attentive eating smartphone application along with standard dietary advice (intervention group) or standard dietary advice only (control group) for 8 weeks. The primary outcomes were change in body weight at 8 weeks and energy intake at 4 and 8 weeks. Additional outcomes included self-reported eating behaviours measured at 8 weeks. Differences between groups were assessed with linear regression (adjusted) using multiple imputation for missing data. Study protocol registered prospectively at (https://doi.org/10.17605/osf.io/btzhw). Results There was no significant difference between the intervention and control group in weight lost at 8 weeks, or change in self-reported 24 h or objective taste-test energy intake at 4 or 8 weeks. Mean weight loss in the intervention group (n = 53) was 1.2 kg and 1.1 kg in the control group (n = 54), adjusted difference of − 0.10 (− 1.6 to 1.3) kg. Self-reported eating behaviours at 8 weeks also did not differ across groups. The intervention was largely used as intended and a per protocol analysis confined to participants in the intervention group that used the attentive eating smartphone application regularly and as intended also showed no effect on energy intake or weight loss. Conclusions A smartphone based attentive eating intervention and standard dietary advice did not result in reduced energy intake or greater weight loss at 4 or 8 week follow-up than standard dietary advice alone. Trial registration ClinicalTrials.gov, NCT03602001. Registered retrospectively on 26th July 2018. Prospectively registered on the Open Science Framework on 11th August 2017.